Persepsi Guru dan Siswa Tentang Penggunaan E-LKPD dalam Penerapan Model Project Based Learning - Ayuni, Indah Tri; Gina, Egina Bumiarti; Evi Roviati (INSTITUT AGAMA ISLAM NEGERI AMBON, 2025)
Students in learning is still using printed books from the library, this causes students to be passive in learning because the material in the printed books that are causes students to be passive in learning because the material in printed books is too broad, complicated and difficult to carry too extensive. Material that is too broad is often not explained by the teacher due to lack of lesson time. Based on this background, a solution is needed to maximize important material to be discussed and in accordance with the learning objectives at each meeting so that the activities to be carried out in learning can be well allocated. The solution to the problem, namely E-LKPD. The purpose of the study was to determine the perceptions of Biology teachers and students towards the use of E-LKPD in implementing learning with the PjBL model. The research method used was descriptive qualitative. The subjects in this study were 1 Biology teacher and 30 students at one of the State High Schools in Cirebon Regency. Data collection techniques used interview sheets, teacher needs analysis questionnaires and student needs analysis questionnaires. The results showed that class X students used learning resources derived from textbooks borrowed from the library, students felt that environmental change material in the textbook was difficult to understand because it was too complex a discussion, the teacher found it difficult to summarize a lot of material from the textbook for several learning objectives. So that according to students and teachers, the package book has not supported learning activities so that it requires other teaching materials that are in accordance with learning objectives and effective content and in electronic form for easy access. Keywords: Requirement Analysis, E-LKPD, PjBL